Expressing Identities in the Basque Arena - MacClancy, Jeremy (World anthropology., 2013)
The author argues that the ethnographic understanding of nationalisms, rather than the orthodox studies of ideology, political parties, social classes and centre-periphery clashes, offers a more nuanced comprehension of the lived reality of people in areas where nationalism is a significant force. Series editors: Wendy James & Nick Allen.